BRUNO-JOFRE, Rosa del Carmen, Methodist Education in Peru: Social Cospel, Politics, and American ldeological and Economic Penetration, 1888- 1930, Wilfrid Laurier Unversity Press (Waterloo, Ontario, Canadá), 1988. 223 p. Bibliografía e ilustraciones. - Klaiber, Jeffrey (Histórica, 1989)
No contiene resumen